Penyuluhan PENYULUHAN PENTINGNYA MENGENALKAN BAHASA INGGRIS PADA ANAK USIA DINI : - - Ambawani, Suprih; Saudah, Siti; Putranti, Bernadetta Eko (LPPM Universitas Al Muslim, 2024)
English language skills need to be mastered as means to prepare human resources to increase individual competitiveness in the global job market. English needs to be introduced from an early age, also known as the